Comparative Assessment of Clinical Skills Potential Assessment of Clinical Skills Using Interactive Methods - Аslonova Ibodat Jabborovna (American Journal of Biomedicine and Pharmacy, 2025)
The observable new wave in optimizing the educational process is undoubtedly linked to the growing interest of educators in interactive learning forms, which act as a springboard for advancing students’ knowledge potential (6, 7, 8). Interactive learning methods (ILMs) include those that require students to independently acquire, process, and apply information presented in a didactic form. Unlike traditional forms, this type of learning significantly enriches the knowledge base while simultaneously enhancing students’ creative thinking potential (9).